THE ROLE OF CULTURAL COMMUNICATION IN THE RAMADHAN FAIR BAZAR TO PROSPERATE THE GREAT MOSQUE IN MEDAN CITY - Siregar, Mahnida Zahra; Ritonga, Muhammad Husni (Program Pascasarjana UIN Sumatera Utara, 2025)
This study analyzes the role of cultural communication of the Ramadhan Fair Bazaar in prospering the Medan Grand Mosque, using qualitative methods with descriptive studies, observation, documentation, and direct interviews. The results of the study indicate that this bazaar is significant in increasing the activeness of the congregation and strengthening social interaction, becoming an annual tradition that has been awaited by the people of Medan City for more than 18 years. The Ramadhan Bazaar also supports the local economy by providing opportunities for MSMEs and facilitating entrepreneurship. In addition, this bazaar plays a role in promoting and preserving local culture, including the tradition of sharing spicy porridge at the Al-Mashun Grand Mosque. Comprehensively, this bazaar activity supports the prosperity of the mosque both physically and non-physically, by increasing visits and community participation and providing a forum for religious and social activities.